The impact of fiscal dominance on macroeconomic performance in Sierra Leone: a DSGE simulation approach - Mohamed Samba Barrie; Emerson Abraham Jackson (West African Journal of Monetary and Economic Integration, 2022)
This study delves into the repercussions of fiscal policies, particularly those marked by high expenditure financed by monetary means, on key macroeconomic indicators in Sierra Leone. Employing a Dynamic Stochastic General Equilibrium (DSGE) model, the analysis illuminates how shocks in one variable ripple through the entire economic system over time. The analysis indicates that high levels of domestic borrowing and monetary financing in the medium-term crowd out private-sector investment hurt growth, and reduce government tax revenues, thereby reducing the government's capacity to invest in public goods and services. Furthermore, it demonstrates that this phenomenon leads to an endless "borrow-to-finance debts expenditures spiral" and creates more debt, worsens macro conditions, and exacerbates fiscal dominance. The paper recommends that policymakers manage Sierra Leone's fiscal trilemma, i.e., high development spending needs, high debt burden, and a low revenue base, not by taking on more debt and relying on monetary financing, but rather by expanding the economy's export capacity, harmonizing fiscal expenditures, and gradually expanding the domestic revenue base. Moreover, to prevent fiscal dominance from becoming systemic in the medium to long term, the research also recommends adhering to the Bank of Sierra Leone 2019 Act, which permits the Bank to cover temporary government deficits at no more than 5% of actual domestic revenue, excluding private receipts in the previous year. In sum, this study underscores the intricate interplay between fiscal policies and macroeconomic stability in Sierra Leone, offering a roadmap for policymakers to navigate the complexities of fiscal and monetary dynamics in the pursuit of enduring economic prosperity. – – Cette étude explore les répercussions des politiques fiscales, en particulier celles marquées par des dépenses élevées financées par des moyens monétaires, sur les indicateurs macroéconomiques clés en Sierra Leone. En utilisant un modèle d'équilibre général stochastique dynamique (DSGE), l'analyse met en lumière comment les chocs dans une variable se propagent à travers tout le système économique au fil du temps. L'analyse indique que des niveaux élevés d'emprunts intérieurs et de financement monétaire à moyen terme évincent les investissements du secteur privé, nuisent à la croissance et réduisent les recettes fiscales du gouvernement, réduisant ainsi sa capacité à investir dans les biens et services publics. De plus, elle démontre que ce phénomène entraîne une spirale sans fin de "s'endetter pour financer les dépenses", créant davantage de dette, détériorant les conditions macroéconomiques et aggravant la dominance fiscale. L'article recommande aux décideurs de gérer le trilemme fiscal de la Sierra Leone, c'est-à-dire les besoins élevés en dépenses de développement, le fardeau élevé de la dette et une faible base de revenus, non pas en contractant davantage de dettes et en comptant sur le financement monétaire, mais plutôt en développant la capacité d'exportation de l'économie, en harmonisant les dépenses fiscales et en élargissant progressivement la base de revenus intérieurs. De plus, pour éviter que la dominance fiscale ne devienne systémique à moyen et long terme, la recherche recommande également de respecter la loi de 2019 de la Banque de la Sierra Leone, qui autorise la Banque à couvrir les déficits temporaires du gouvernement à hauteur de 5 % maximum des recettes intérieures réelles, en excluant les recettes privées de l'année précédente. En résumé, cette étude souligne l'interaction complexe entre les politiques fiscales et la stabilité macroéconomique en Sierra Leone, offrant ainsi un guide aux décideurs pour naviguer dans les complexités des dynamiques fiscales et monétaires dans la poursuite d'une prospérité économique durable.
Keywords: E3; E5; H6; O2; 330; Fiscal Dominance; macroeconomic variables; Sierra Leone; DSGE Framework; Monetary Financing